ANALISIS BOBOT PEMILIHAN SUPPLIER BAHAN BAKAR MINYAK UNTUK KAPAL PENGANGKUT BATUBARA DENGAN METODE ANALYTIC HIERARCY PROCESS - Arie Bakhtiar (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
The analytical Hierarchy process (AHP) is a multicriteria decision making approach can be used to solve complex decision problems. This study aimed to use this objective tool to build ship fuel suppliers' selection model, utilizing competitive priorities administrative requirement, quality, delivery, finance, technical and price as an evaluation and selection criteria. The researcher has developed an evaluation questionnaire distributed to couple functional managers in the shipping company. This study concluded that the price is the most important criterion among competitive priorities criteria for selecting and evaluating suppliers as it got a percentage of 0.202, followed by technical criterion that got a percentage of 0.197 and finance got 0,191. Other criterion was quality that got 0.169 followed by delivery with 0.133 and the last criterion was administrative requirement with 0.108.